Niveles de ácido naftalen acetico (ANA) y ácido indol butírico en la propagación vegetativa de mora (Rubus glaucus Benth). - Chugchilan Toaquiza, Nelson (2011)
This work was done in the parish of Hope, Canton Pujilí, province of Cotopaxi, whose geographical location is at 0 °, 41, 00 "south latitude and 79 °, 06 ', 00' west longitude at an altitude of 1800 m, and lasted 45 days. The purpose of this study is to assess hormone levels and AIB ANA in the spread of blackberry (Rubus glaucus benth) rooting stimulators, the naphthaleneacetic acid (NAA) and indole - butyric acid (IBA), in doses of 2000 mg kg ֿ ¹ ANA + 2000 mg kg ֿ ¹ AIB, 1500 mg kg ֿ ¹ ANA + 1500 mg kg ֿ ¹ AIB, 1000 mg kg ֿ ¹ ANA + 1000 mg kg ֿ ¹ AIB, and a control without hormones that are in treatment studies. We used a completely randomized design (DCA) with 4 treatments and 4 repetitions, with 30 experimental units in each treatment, after 45 days were evaluated the mortality rate, percentage of rooting, root number, root length (cm), number of shoots and shoot length, applying the Tukey test to determine significant differences between treatment means. Hormone therapy 2000 mg kg ֿ ¹ ANA + 2000 mg kg ֿ ¹, of AIB which had the best rates on all variables that were studied have a benefit / cost ratio of 1.96 USD, giving a return on this treatment 196.20 %. This research demonstrated that auxins are necessary to stimulate root formation in cuttings of mora and get better rooting.